Loss of expression of the tumour suppressor gene AIMP3 predicts survival following radiotherapy in muscle‐invasive bladder cancer. Issue 3 (22nd July 2014) - Gurung, Pratik M.S.; Veerakumarasivam, Abhi; Williamson, Magali; Counsell, Nicholas; Douglas, James; Tan, Wei S.; Feber, Andrew; Crabb, Simon J.; Short, Susan C.; Freeman, Alex; Powles, Thomas; Hoskin, Peter J.; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to test the utility of AIMP3, an upstream regulator of DNA damage response following genotoxic stress, as a clinical biomarker in muscle‐invasive bladder cancer (MIBC). AIMP3 was identified from a meta‐analysis of a global gene‐expression dataset. AIMP3 protein expression was determined by immunohistochemistry on a customised bladder cancer tissue‐microarray (TMA). The mechanism of gene silencing was probed using methylation‐specific PCR. The association between AIMP3 expression, Tp53 transactivity and genomic stability was analysed. In vitro AIMP3 translocation to the nucleus in response to ionising radiation was demonstrated using immunofluorescence. Radiosensitisation effects of siRNA‐mediated AIMP3‐knockdown were measured using colony forming assays. TMAs derived from patients enrolled in BCON, a Phase III multicentre radiotherapy trial in bladder cancer (ISRCTN45938399) were used to evaluate the association between AIMP3 expression and survival. The prognostic value of AIMP3 expression was determined in a TMA derived from patients treated by radical cystectomy. Loss of AIMP3 expression was frequent in MIBC and associated with impaired Tp53 transactivity and genomic instability. AIMP3‐knockdown was associated with an increase in radioresistance. Loss of AIMP3 expression was associated with survival in MIBC patients following radiotherapy (HR = 0.53; 95% CI: 0.36 to 0.78, p = 0.002) but was not prognostic in the cystectomy set. In conclusion, AIMP3 expression is lost in a subset of bladder cancers and is significantly predictive of survival following radiotherapy in MIBC patients.